The benefit of an effective safety program in the agribusiness industry - Carey, Christopher Miles (Kansas State University, 2007)
This thesis is the tool for moving companies to the next level in safety. I believe through this plan we can keep people safe in the agribusiness industry. This is very important, so that we can keep cost down and be able to stay in business; or avoid costly litigation / arbitration hearings because someone was injured on the job. When I was hired my job was to develop procedures that meet Occupational Safety and Health Administration (OSHA) standards, reduced injuries, and would be a continuous improvement type of program. The thesis will be introductory information in regards to safety followed by a sample safety manual that I have created by working with different safety professional in the safety industry.
Keywords: workplace safety; OSHA; Manufacturing; Accidents; Continuous Improvement; Agriculture, General (0473); Business Administration, Management (0454); Health Sciences, Occupational Health and Safety (0354)